Implementasi Algoritma Selection Sort dan First Come First Served Dalam Sistem Reservasi Paket Wisata - Tito Rizki Purnomo; Maimunah, Maimunah; Pristi Sukmasetya (STMIK Budi Darma, 2024)
Candirejo Village is located in Borobudur District, also known as Candirejo Tourist Village. KOPERASI WISATA was established for the purpose of managing tourist destinations at the village.One of the tourism destination is named Nagari Wayang Kertas which located at Dusun Sangen. All the tourist comes to the village have to go through process from the thirds party which called KOPERASI WISATA. Those causes the arrival process innefective because they can not directly contacting the owner of the tourism destination. Solving this problem, designing a web-based reservation system for Nagari Wayang Kertas facilitating the booking process would improve the time efficiency required for reservations. The methods of data collecting in this research includes observation, interviews, and literature review. The software development process itself using the Rapid Application Development (RAD) method due to its high success rate in software development. The implemented algorithms which used in this research are Selection Sort and First Come First Served maximizing the efficiency of the reservation process for visitors. Before being tested and implemented to the users, the testing system uses the black-box testing method. The results of the testing method showing that the function of the designed system works and operates as expected and needed